1981
DOI: 10.1177/104438948106200903
|View full text |Cite
|
Sign up to set email alerts
|

The Adjustment of Black Children Adopted by White Families

Abstract: A study has found that, initially, transracially placed children are more maladjusted than their inracially adopted peers. Yet, when age at placement is taken into account, the differences disappear. Thus, transracial adoption may continue to be a viable option for the many nonwhite children awaiting placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We will use the umbrella term of "satisfactory outcome" when the children had overall adjustment in terms of educational attainment, peer relations and behaviour, equal to or better than comparison groups or normative standards for the assessment tools used. U.S.A. studies quote satisfactory outcomes for more than 70% of the sample (Barth & Berry, 1988;Fanshel, 1972;McRoy et al, 1982;Shireman & Johnson, 1986;Silverman & Feigelman, 1981;, 1981. Even higher rates are quoted in the U.K. studies (Bagley, 1993a, b;Bagley & Young, 1979;Gill & Jackson, 1983).…”
Section: Psychological Questionsmentioning
confidence: 99%
“…We will use the umbrella term of "satisfactory outcome" when the children had overall adjustment in terms of educational attainment, peer relations and behaviour, equal to or better than comparison groups or normative standards for the assessment tools used. U.S.A. studies quote satisfactory outcomes for more than 70% of the sample (Barth & Berry, 1988;Fanshel, 1972;McRoy et al, 1982;Shireman & Johnson, 1986;Silverman & Feigelman, 1981;, 1981. Even higher rates are quoted in the U.K. studies (Bagley, 1993a, b;Bagley & Young, 1979;Gill & Jackson, 1983).…”
Section: Psychological Questionsmentioning
confidence: 99%
“…Several of those studies' findings reveal that Black children adopted transracially have maladjustment problems (Feigelman & Silverman, 1984;Silverman & Feigelman, 1981). However, other researchers (Bagley, 1993;Grow & Shapiro, 1974;Shireman & Johnson, 1986) have reported that they have found no differences between adjustment levels of children adopted by same-ethnicity parents and those whose adoptive parents are of a different ethnicity.…”
Section: Overview Of the Transracial Adoption Controversymentioning
confidence: 90%
“…Assessing validity of the concerns of MEPA opponents, some agencies note that to consider the best interest of the child, "a range of nurturing homes should be considered, and gay and lesbians are a valuable resource" (Donaldson Adoption Institute, 2006, p. 6;Child Welfare League of America, 2004). Silverman & Feigelman (1981) found that to delay placements is more detrimental than any deleterious outcomes due to transracial adoption. Addressing the initial controversies of MEPA opponents that transracial adoption is detrimental to racial identity, Simon, Alstein, and Melli (1994) concluded that transracial adoptees are aware of their racial identity, comfortable with it, and are emotionally and socially adjusted.…”
Section: Overview Of the Transracial Adoption Controversymentioning
confidence: 95%
“…It shares with those opposed to transracial adoption an individual psychological paradigm and assumes that conceptualisations of the self, self-esteem and identity are relatively unproblematic and open to measurement. They conclude that, in general, transracially adopted children do not develop either identity or adjustment problems (Simon, 1974;Kirk, 1981;Silverman & Feigelman, 1981) or negative attitudes to black people. Nevertheless, despite the diversity in sample construction and size, the age range of the subjects and the variety of methods used, there is striking consistency between the findings which merits closer attention.…”
Section: Empirical Research Findingsmentioning
confidence: 99%
“…Under this ruling anyone with a black ancestor was classified as black, no matter how white in appearance. 1979Silverman & Feigelman. 'Because there is a black member of the family, albeit several generations apart, our assessment of the [biological] family is that they are of mixed race.…”
Section: Notesmentioning
confidence: 99%